Inheritances in Austria: A model estimation of intergenerational wealth transfers up to 2050 - Klaus Grünberger; Judith Derndorfer; Mattias Schnetzer (European Commission, Joint Research Centre (JRC), 2024)
Since the end of inheritance and gift tax in 2008, there has been hardly any data on the distribution and volume of inheritances in Austria. Voluntary household surveys capture past inheritances, but there is a lack of current values as well as forecasts on the future development of inheritances. Using data from the Household Finance and Consumption Survey (HFCS) and the microsimulation model INTAXMOD, this paper estimates the annual inherited wealth and the potential tax revenue up to 2050. The results show (a) a doubling of the annual inheritance volume between 2025 and 2050 from approximately exteuro21 to 41 billion, (b) a strong concentration in the upper percentile of the inheritance distribution, and (c) potential tax revenues of over exteuro1 billion per year from inheritance taxes with tax exemption of exteuro1 million.
Keywords: 330